NiSe2 nanooctahedra as anodes for high-performance sodium-ion batteries. (31st July 2019) - Fan, Siwei; Li, Guangda; Yang, Gai; Guo, Xu; Niu, Xinhuan
Abstract : Octahedral NiSe2 was fabricated by a facile hydrothermal method. It showed excellent Na ion storage performance when used as an anode material for sodium-ion batteries. Abstract : Herein, NiSe2 nanooctahedra (NiSe2 -NO) were fabricated by a two-step facile hydrothermal method, and the side length of the octahedra was about 400 nm. Moreover, the formation mechanism of the octahedra was examined by changing the selenization time and the species and concentration of alkaline hydroxide. NiSe2 -NO shows excellent Na ion storage performance when used as an anode material for sodium-ion batteries (SIBs). It delivers the high reversible capacity of 462.1 mA h g −1 after 500 cycles at the current density of 1 A g −1, and even at the higher current density of 5 A g −1, the capacity still could reach 191.1 mA h g −1 after 1000 cycles. Furthermore, the initial coulombic efficiency was more than 80% at various current densities. These excellent electrochemistry properties can be attributed to the synergistic effects between the octahedra and the polyhedron particles on the surfaces of the octahedra.